IMPLEMENTASI KEBIJAKAN OTONOMI KHUSUS (STUDI KASUS TENTANG PELAYANAN PUBLIK BIDANG PENDIDIKAN) DI KABUPATEN LANNY JAYA PROVINSI PAPUA - Tabuni, Depinus; Rumapea, Patar; Areros, William Agustinus (Sam Ratulangi University, 2016)
Giving Policy Special Autonomy for Papua Province which is based on Law No. 21 of 2001 on the policy of this Special Autonomy in essence has the government's goal centere authority for the Papuan people to manage their own natural resources are owned and given the devolution of responsibility to promote, accelerate development both in terms of political, economic, cultural, and social welfare. Therefore, education is very important for every citizen of Indonesia. Department of Education that works must actively participate in policy implementation public services, starting with kindergarten elementary, junior high through high school/vocational school. One of the challenges faced by the Government of Papua Province, more specifically in the district of Lanny Jaya maximize the level of education of the Papuan people in addressing the issue of lagging development in various sectors in the district of Lanny Jaya, especially on the development of quality education, both natural resources and human resources, so that able to reduce the problem of underdevelopment and social welfare and creating a quality society. This study aimed to analyze the implementation of special autonomy policy in education in the District of Lanny Jaya Papua Province.This study used a qualitative design, which focused on the implementor communication, the sources of policy implementation, trends relating to the impact of dispositions, the appointment of bureaucrats and bureaucratic structures executor/organizer. The primary data obtained through observations through interviews with 10 informants consists of 6 people from relevant agencies and the 4 elements in society who are knowledgeable about education, and supported by studies related documentation. The data were processed and analyzed through the stages of categorization, data reduction, data grouping, which in turn are arranged in the form of narratives, data interpretation, and conclusions based on the arrangement of the narrative, and to verify the results of the data with the informant that is based on the conclusions.The results showed that the communication is done over emphasize internal communications in which the government should have to provide space for the community so that the implementation of policies run under Law No. 21. 2001 on special autonomy. Organizations in solving the educational bureaucracy is not in the communication to introduce and disseminate the existence and the services performed in connection with education services in the general population. Factors human resources in education both in quality and quantity still tranquility, given the lack of qualified human resources factor even sumbedaya development. Factors disposition in performing work based more responsibility as a government to run the administrative functions not serving the public do not even run a bureaucratic administrative functions for education in the interior. Bureaucratic structure which is operationally services, namely education and training section and a public service that reflects the service as contained in the basic tasks, functions and scope of activities defined, and not supported standard operating procedures (SOP) as a working guideline implementation of the special autonomy.The study concluded that the implementation of special autonomy in Papua Province District Lanny Jaya is not maximized in efforts to achieve a healthy society, cultured, qualified and independent in realizing the various aspects of the construction of more specialized education. It is recommended that education should be improved communication media such as newspapers, radio, banners, brochures and billboards about the existence of special autonomy, and need socialization of all theimplementation of the measures taken, it is necessary to do the evaluation, supervision and planning and services clear implementation of the Law on Special Autonomy for Papua. 21 in 2001. In addition, it should be added helpers bureaucracy by considering appropriate educational background with the required fields. Perluh pulah attempted to placed the public service means more strategic and easily accessible by the public. Outlines the main duties and functions based on a clear organizational structure, as well as reorganize the organizational structure with more focus on the technical and operatin standard